Friedrich D.E. Schleiermacher´s ethics of individuality (Research, Society and Development, 2020)
The aim of this article is to develop elements for analyzing the first intellectual efforts from one of the greatest philosophers and theologians of the modern period, namely, Friedrich D.E. Schleiermacher. Such elements will be at the heart of the development of the German philosopher's ethical thought. At first, Schleiermacher will constantly dialogue with the Kantian ethical system, from this dialogue some fundamental elements of his thinking will emerge. The central element of Schleiermacherian criticism of the Kantian ethical system revolves around the incomprehensibility of the concept of transcendental freedom. If human action is a problem, then it must be able to be completely thought out in the phenomenal realm, and the postulation of the numerical realm is unnecessary. Therefore, it will be shown how Schleiermacher tries to offer his alternative to Kantian ethics. This attempt will be made through the constant tension between rationality and sensitivity. Later, his own ethical conception will be presented as an ethics of individuality. Schleiermacher will discuss the experience of forming his own individuality. An individuality that must be in connection with the other individualities and with the Infinite.